Analysis of Factors Associated With Depression in Community-Dwelling Older Adults in Wuhan, China - Liu, Aihong; Peng, Yingjie; Zhu, Wenli; Zhang, Yanling; Ge, Shihui; Zhou, Yun; Zhang, Kemeng; Wang, Zhaohui; He, Ping (Frontiers in Aging Neuroscience, 2021)
Objectives: This study aimed to identify the independent factors associated with depression in community-dwelling older adults in Wuhan, China. Methods: Four hundred and seventy older adults (aged ≥65 years) from four communities dwelling on Junshan Street in Wuhan, China were included in this study. Participants completed a questionnaire that asked questions pertaining to age, gender, educational level, income, living situation, care situation, social support, and social engagement. The 30-item Geriatric Depression Scale (GDS-30), the Fried frailty phenotype scale, the activities of daily living (ADL) scale, the mini nutritional assessment scale-short form (MNA-SF), and the Mini-cog scale were used to assess depression, frailty, self-care ability, malnutritional risk, and cognitive dysfunction, respectively. Differences in age, gender, educational level, income, living situation, care situation, social support, social engagement, ADL score, risk of malnutrition, frailty, and cognitive dysfunction between the non-depression (GDS-30 score <10 points) and depression groups (GDS-30 score ≥10 points) were compared using a chi-square test. Moreover, correlations between factors and depression were analyzed using Pearson’s correlation. Then, significant variables (p < 0.05) from the chi-square test were included in a multivariable logistic regression model to identify the independent factors associated with depression. Results: The incidence of depression among the participants was 14.04%. Age (p < 0.001), educational level (p < 0.001), living situation (p < 0.001), social support (p = 0.001), ADL score (p = 0.023), frailty (p < 0.001), and cognitive dysfunction (p < 0.001) were all significantly associated with depression, in which age, poor social support, frailty, and cognitive dysfunction were identified as independent factors. Conclusion: Improving social support and effective interventions for frailty and cognitive dysfunction may help relieve depression in community-dwelling older adults.